Loved to the End - The Path to Holiness in Married Life: Yêu Đến Cùng - Con Đường Nên Thánh Trong Đời Sống Hôn Nhân - Nguyen, Trong Tin (Khoa Học Công Giáo và Đời Sống, 2023)
The purpose of this study is to ensure that all are bonded together" in the Church with a love that endures, enabling them to fulfill God's lovely dream of families: "the will to build a family is the courage to participate in God's dream, to dare to dream with Him, to dare to build with him, to dare to play with him in this history, to build a world in which no one feels alone." May each of our Christian families, with the guidance of the Holy Spirit, realize and embrace their extraordinarily noble calling to holiness and to becoming the Triune Family of God with unwavering love, so that they will be able to honor the Name of God in their family: The name we have always believed in. It's "Love".